The Influence of Service Quality and Employee Performance on Customer Satisfaction in the Maja Langu Savings and Loan Cooperative, Denpasar - Anak Agung Ngurah Bagus WIRAGUNA; A. A. Sri PURNAMI; A.A Ketut JAYAWARSA; I Gusti Ayu Athina WULANDARI (PT. Keberlanjutan Strategis Indonesia, 2023)
Purpose:In the competitive business world, customer satisfaction is the main focus for companies. It is not just a goal but also the key to attracting and retaining consumers. This study investigates the influence of service quality and employee performance on customer satisfaction at the Maja Langu Savings and Loans Cooperative, Denpasar.Methodology:64 respondents were successfully obtained by applying the purposive random sampling method and considered representative of the overall sample. Data analysis was carried out using multiple linear regression after undergoing instrument and classical assumption tests. The approach used is quantitative, with a questionnaire as the data collection instrument.Findings:The research results show that service quality and employee performance positively and significantly impact customer satisfaction at KSP Maja Langu, Denpasar. These two factors individually have a positive and significant influence on customer satisfactionImplication:These findings have important implications for the management and employees of KSP Maja Langu in maintaining and increasing customer satisfaction. Improving service quality and employee performance will help increase customer satisfaction at the Maja Langu Denpasar Savings and Loans Cooperative.